Evaluating the effect of a 12-month youth advisory group on adolescent’s leadership skills and perceptions related to chronic disease prevention research: a mixed-methods study - Mariam Mandoh; Rebecca Raeside; Allyson Todd; Julie Redfern; Seema Mihrshahi; Hoi Lun Cheng; Philayrath Phongsavan; Stephanie R Partridge (BMC Public Health, 2023)
Abstract Background Youth Advisory Groups (YAGs) represent a promising method to engage adolescents in research of relevance to them and their peers. However, YAGs are rarely implemented or evaluated in chronic disease prevention research. The aims of this study were firstly, to evaluate the effect of participation in a 12-month YAG on adolescents’ leadership skills and perceptions related to chronic disease prevention research and secondly, to evaluate the process of establishing and facilitating a 12-month YAG and identify barriers and enablers to establishment and facilitation. Methods This study was a 12-month pre-post study. Eligible participants were adolescents (13-18-years) and current members of an established YAG. Data collection involved online surveys and semi-structured interviews at baseline, six-months and 12-months follow-up. Participatory outcomes such as self-efficacy, leadership skills, and collective participation were derived from Youth Participatory Action Research Principles (YPAR), and the Lansdown-UNICEF conceptual framework for measuring outcomes of adolescent participation. Process evaluation data were captured via meeting minutes, Slack metrics and researcher logs. Quantitative data was analysed using descriptive statistics and qualitative data was thematically analysed using a reflexive thematic analysis approach. Results Thirteen (13/16) YAG youth advisors consented to participate in the evaluation study (mean age 16.0 years, SD 1.3; 62% (8/13) identified as female). Survey data assessing participatory outcomes found an increase in leadership and life skills scores over 12-months (+ 8.90 points). Semi-structured interview data collected over the 12-month term revealed three key themes namely: influence, empowerment, and contribution. Comparison of pre-post themes determined a positive trend at follow-ups, demonstrating improved participatory outcomes. Process indicators revealed that at 12-month follow-up the YAG was implemented as planned. Semi-structured interview data determined barriers to YAG facilitation included time and limited face-to-face components, while enablers to YAG facilitation included flexibility, accessible delivery methods, and a supportive adult facilitator. Conclusion This study found that a YAG fostered positive participatory outcomes and unique opportunities for youth participants. A successful YAG based on YPAR principles requires researchers to ensure YAG establishment and facilitation is an iterative process. Taking into consideration important barriers and enablers to YAG facilitation ensures adolescent engagement in a YAG is both meaningful and impactful.